No Association of Genetic Markers with Carotid Intimal Medial Thickness in β-Thalassemia Major Patients - Singh, Mable Misha; Kumar, Ravindra; Tewari, Satyendra; Agarwal, Sarita (Journal of Pediatric Genetics, 2018)
Regular transfusion leads to cardiac siderosis resulting in cardiac complications that account for more than 71% of the total mortality in thalassemia patients. We aimed to study the variants of matrix metalloproteinase-9 (MMP9), matrix Gla protein (MGP), and estrogen receptor α(ERα), which might be contributing to atherosclerosis, leading to heart failure in thalassemia major. One hundred and five thalassemia patients on regular transfusion and iron chelation therapy were enrolled for the study. Carotid artery intimal medial thickness (CIMT) measurement was done to check for atherosclerosis. MMP9 (C1562T), MGP (T138C), and ERα gene (PvuII (rs2234693T > C) and XbaI (rs9340799A > G) polymorphism were analyzed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method. CIMT values were within the normal range (<0.90 mm) in all patients. There was no difference in mean CIMT values between males and females (0.56 ± 0.11 versus 0.56 ± 0.12, p = 0.928). There was no correlation of CIMT with age, body surface area, and body mass index as well as with serum ferritin levels. No statistically significant difference in frequency of MMP9, MGP, and ERα genotypes was seen in two dichotomized groups of CIMT (CIMT < 0.56 and CIMT ≥ 0.56). Variants of MMP9, MGP, and ERα have a reserved influence on cardiac disease pathogenesis, and the disease phenotype in thalassemia patients may be more strongly impacted by other factors.
Keywords: β-thalassemia major; MMP9; MGP; ERα; CIMT